The Antiplatelet Effects of a New Nitroderivative of Acetylsalicylic Acid - An In Vitro Study of Inhibition on the Early Phase of Platelet Activation and on TXA2 Production - Lechi, Clara; Andrioli, Giuseppe; Gaino, Stefania; Tommasoli, Rosamaria; Zuliani, Valeria; Ortolani, Riccardo; Degan, Maurizio; Benoni, Giuseppina; Bellavite, Paolo; Lechi, Alessandro; Minuz, Pietro (Thrombosis and Haemostasis, 1996)
We studied in vitro the antiplatelet activity of a new nitroderivative chemically related to acetylsalicylic acid: 2 acetoxybenzoate 2-[l-nitroxy-methyl]-phenyl ester (NCX 4016), in order to identify any effects due to the release of nitric oxide and the blockade of cyclooxygenaseThe effects of scalar doses of NCX 4016 on the early phase of platelet activation, platelet aggregation and thromboxane A2 production were investigated. We observed inhibitory effects of NCX 4016 on platelet adhesion (IC50 = 7.3 × 10−5 M), platelet cytosolic calcium concentration, assayed by fluorescent probe Fura 2, and the expression of glycoprotein IMIIa (CD41 / αIIbβ3) (IC50 = 3.4 × 10−5 M) and P-selec-tin (CD62 / GMP-140) (IC50 = 4.9 × 10−5 M) measured by flow cytometry. NCX 4016 also prevented thrombin-induced platelet aggregation (IC50 = 3.9 × 10−5 M). None of these parameters were affected by acetylsalicylic acid. These inhibitory activities of NCX 4016 were abolished by oxyhaemoglobin and methylene blue. Intracellular cyclic GMP observed during thrombin-induced aggregation was increased by incubation with NCX 4016. These results appear to be attributable to the release of nitric oxide, which activates soluble platelet guanylyl-cyclase and promotes intracellular cyclic GMP increase. NCX 4016 almost completely inhibited platelet thromboxane A2 production and arachidonic acid-induced platelet aggregation. This also occurred in the presence of oxyhaemoglobin and methylene blue, indicating that its antiplatelet activity can be attributed not only to nitric oxide release but also to cyclo-oxygenase inhibition.